Flavonoid Compound from Dichloromethane Extract of Crinum amabile Donn Leaves - Andika Wahyu Afrianto; Kanda Panthong (Kaunia: Integration and Interconnection Islam and Science Journal, 2022)
Flavonoid compound was isolated from Crinum amabile Donn. leaves. The separation of flavonoids was carried out by using chromatographic techniques to purify CH2Cl2 extract of Crinum amabile Donn. leaves. Column chromatography with silica gel and sephadex as stationary phases, thin-layer chromatography, and preparative thin-layer chromatography were the chromatographic techniques used in this research. The pure compound obtained in the form of white-yellow solid with the Rf value is 0.44. Compound identification using 1H-NMR spectrometer showed the presence of protons from the CH=CH ortho with the appearance of a doublet of doublet (dd) each having j values of 8.5 Hz and 8.1 Hz with chemical shifts in the range of 6.5 ppm and 7 ppm. The CH=CH ortho group with the appearance of doublet of doublet of doublet (ddd) each having j values 8.4 Hz and 9 Hz with chemical shifts in the range of 7.2 ppm to 7.4 ppm. The methoxy group (-OCH3) was detected on chemical shift 3.8 ppm. Spectrometries of analysis showed that flavonoid compound obtained was 4-Hydroxy-7-Methoxyflavan.